A potential endemic cyprinid for aquaculture and food security: the embryonic development of the Bornean spotted barb Puntius sealei (Herre, 1933) - Abit, Lirong Yu; Unggang, Edmond Felix; Al Asif, Abdulla; Latif, Kamil (Ebu Press, 2021)
The Bornean Spotted Barb is endemic fish species and widely distributed throughout Borneo in various freshwater bodies and can be considered as a potential aquaculture candidate for food security and the ornamental trade. However there has yet to be scientific studies on the early life history and developmental stages of this species. Thus the present study reveals the embryonic development of Puntius sealei embryo, from fertilization to post-hatching using the induced breeding method. The induced spawning on P. sealei using Ovaprim hormone at a dose of 0.5 ml/kg for females and 0.25ml/kg for males respectively was successfully conducted and the embryonic development of the fertilized eggs were observed. The zygote, cleavage, blastula, gastrula, segmentation, and larval phases were the six major stages of embryogenesis that investigated in this experiment. This study contributed major knowledge to the early developmental biology of this particular species. The information will be useful for accessing the potentiality of this species for aquaculture as well as the management, and production of the species.